2018
DOI: 10.1002/aelm.201700481
|View full text |Cite
|
Sign up to set email alerts
|

On the “True” Structure of Push–Pull‐Type Low‐Bandgap Polymers for Organic Electronics

Abstract: Donor-acceptor type conjugated polymers are a dominating class of active materials in the field of organic electronics. Their adjustable light-harvesting, charge transfer and charge transport characteristics are beneficially applied in organic photovoltaics, photodetectors and thin-film transistors. The conventional synthetic approach toward these push-pull polymers is based on Suzuki or Stille cross-coupling of complementary functionalized (hetero)aromatic monomers. In the ideal world, this gives rise to a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 76 publications
0
52
0
Order By: Relevance
“…It was assumed that conjugated polymers prepared via these techniques were comprised exclusively of a perfectly alternating backbone due to the monomers' complementary functional groups. However, a number of studies have since revealed that these structures are far from “defect‐free”: homocoupling side‐products are widespread in polymers synthesized by these well‐established coupling techniques and they have a clear detrimental effect on the quality of devices prepared from these polymers . Even in small molecule couplings, such side‐reactions can be readily identified.…”
Section: Elucidating the Quality Of Polymers Prepared By Direct Arylamentioning
confidence: 99%
“…It was assumed that conjugated polymers prepared via these techniques were comprised exclusively of a perfectly alternating backbone due to the monomers' complementary functional groups. However, a number of studies have since revealed that these structures are far from “defect‐free”: homocoupling side‐products are widespread in polymers synthesized by these well‐established coupling techniques and they have a clear detrimental effect on the quality of devices prepared from these polymers . Even in small molecule couplings, such side‐reactions can be readily identified.…”
Section: Elucidating the Quality Of Polymers Prepared By Direct Arylamentioning
confidence: 99%
“…Homocoupling reactions are known to occur in the Suzuki, 12 Stille, 13 and direct arylation 14 crosscoupling polycondenstation reactions that are commonly used to synthesize donor-acceptor small-molecules and polymers that nd widespread use organic solar cells. The topic of structural defects is nding increasing awareness and was recently reviewed by Maes et al 15 The homocoupling of two bromide monomers in the Suzuki and Stille polymerization reaction in low band gap diketopyrrolopyrrole (DPP) polymers has previously been investigated in our group in some detail. 16 The defect is caused by homocoupling of two brominated dithienyl-diketopyrrolopyrrole (T-DPP-T) units, creating T-DPP-2T-DPP-T defects in the polymer main chain.…”
Section: Introductionmentioning
confidence: 99%
“…Even upon applying “nearly perfect” conditions, e.g., an oxygen‐free atmosphere and a proper Pd‐ligand stoichiometry, homocoupling between either two organotin/boron or two arylhalide units can occur . The importance and possible abundance of these misscoupled structural units for the performance of the organic solar cells has only recently been recognized and a few reports on this have appeared …”
Section: Introductionmentioning
confidence: 99%